Contribution of Colonic Fermentation and Fecal Water Toxicity to the Pathophysiology of Lactose-Intolerance - Windey, Karen; Houben, Els; Deroover, Lise; Verbeke, Kristin (Nutrients, 2015)
Whether or not abdominal symptoms occur in subjects with small intestinal lactose malabsorption might depend on differences in colonic fermentation. To evaluate this hypothesis, we collected fecal samples from subjects with lactose malabsorption with abdominal complaints (LM-IT, n = 11) and without abdominal complaints (LM-T, n = 8) and subjects with normal lactose digestion (NLD, n = 15). Lactose malabsorption was diagnosed using a 13C-lactose breath test. Colonic fermentation was characterized in fecal samples at baseline and after incubation with lactose for 3 h, 6 h and 24 h through a metabolomics approach using gas chromatography-mass spectrometry (GC-MS). Fecal water cytotoxicity was analyzed using a colorimetric assay. Fecal water cytotoxicity was not different between the three groups (Kruskall-Wallis p = 0.164). Cluster analysis of the metabolite patterns revealed separate clusters for NLD, LM-T and LM-IT samples at baseline and after 24 h incubation with lactose. Levels of 5-methyl-2-furancarboxaldehyde were significantly higher in LM-IT and LM-T compared to NLD whereas those of an unidentified aldehyde were significantly higher in LM-IT compared to LM-T and NLD. Incubation with lactose increased short chain fatty acid (SCFA) concentrations more in LM-IT and LM-T compared to NLD. In conclusion, fermentation patterns were clearly different in NLD, LM-IT and LM-T, but not related to differences in fecal water cytotoxicity.